The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/pbc.27034
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden and conditioning regimens in ASCT1221, a randomized phase II trial in children with juvenile myelomonocytic leukemia: A Children's Oncology Group study

Abstract: The regimen of Bu-Flu is inadequate to provide disease control in patients with JMML who present to HCT with large burdens of disease. Advances in molecular testing may allow better characterization of biologic risk, pre-HCT responses to chemotherapy, and post-HCT management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…At the University of California San Francisco (UCSF) Benioff Children's Hospital, the institutional bias has been to treat JMML patients with moderately intense, well‐tolerated myeloid‐based chemotherapy to try and reduce disease burden prior to transplant. Data from a Children's Oncology Group transplantation study showed that pre‐HCT chemotherapy (performed at the discretion of the provider) did yield molecular remissions; however, the number of patients was small and the study not powered to address this question …”
Section: Introductionmentioning
confidence: 99%
“…At the University of California San Francisco (UCSF) Benioff Children's Hospital, the institutional bias has been to treat JMML patients with moderately intense, well‐tolerated myeloid‐based chemotherapy to try and reduce disease burden prior to transplant. Data from a Children's Oncology Group transplantation study showed that pre‐HCT chemotherapy (performed at the discretion of the provider) did yield molecular remissions; however, the number of patients was small and the study not powered to address this question …”
Section: Introductionmentioning
confidence: 99%
“…
To the Editor Juvenile myelomonocytic leukemia (JMML) is an aggressive myeloproliferative neoplasm of childhood with nearly half of all patients relapsing within 3 years [1,2]. More than 90% of JMML patients present with initiating mutations in NF1, KRAS, NRAS, RRAS, RRAS2, CBL, and PTPN11, all leading to hyperactivation of the Ras pathway [3].
…”
mentioning
confidence: 99%
“…To demonstrate the platform’s potential utility in personalized medicine, a droplet digital PCR (ddPCR) assay that was previously designed for precision monitoring of a specific patient was replicated on the novel digital PCR platform. Juvenile myelomonocytic leukemia (JMML) is an aggressive myeloproliferative neoplasm of childhood with nearly half of all patients relapsing within three years 17,18 . A seven-week-old boy diagnosed with JMML was shown to have WT status for all known JMML mutations.…”
Section: Resultsmentioning
confidence: 99%
“…Given the novelty of this CCDC88C - FLT3 fusion, no commercial assays were available to identify fusion transcripts below the sensitivity of cytogenetics. As such, the oncologist designed a specific ddPCR assay to analyze the abundance of this CCDC88C - FLT3 fusion in peripheral blood RNA over serial time points 18 . This ddPCR-based method for monitoring the patient’s response to Sorafenib (Nexavar) enabled the patient to proceed safely to hematopoietic stem cell transplantation (HSCT) and eventually achieve a complete molecular remission.…”
Section: Resultsmentioning
confidence: 99%